EXPLORATION OF RBC AND HGB IN MENCIT (Mus musculus) HYPEROLOLERINOLEMIA - Nofisulastri Nofisulastri; Baiq Mirawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
So far there is no clear information about RBC and HGB linkage with hypercholesterolemia, especially for arteriosclerosis and hypertension patient. In the future, this research is expected to add a repertoire of knowledge and people knew about hypercholesterolemia and the utilization of appropriate alternative medicine. A total of 20 mice (Mus musculus) age ± 2 months of hypercholesterolemia caused by cholesterol-rich diet (ad libitum). The data were analyzed by analysis of variance based on Randomized Block Design (RAK) 1% with 5 (five) groups and 4 replications (positive control, negative group, and the group of celery extract dose 0,5 ml with concentration 25%, 50%, 100%). It was concluded that HGB in line with RCB (either treated with celery extract or mice treated with hypercholesterolemia) and the provision of celery extract significantly did not affect RBC and HGB with total blood cholesterol level of mencit.